Predictive Influence of Psychological and Educational Adjustments on Internally Displaced Students’ Physics Ability - Ellah, Barnabas Obiaje (EDUPEDIA PUBLISHER, 2025)
Purpose: This study investigated the predictive capacity of psychological and educational adjustments on the cognitive ability levels in Physics among internally displaced students in Nigeria. Methodology: Grounded in the social exclusion theories of Pacione (1997) and Walker (1997), the research employed a correlational survey design. The target population comprised internally displaced persons (IDPs)—including women, adolescents, and children—in Adamawa State. A systematic sampling technique was utilized to select a representative sample of 900 respondents. Data collection instruments included the Ability Group Test (AGT), Literacy and Numeracy Scale (LNS), Communal Trauma Event Inventory (CTEI), Satisfaction with Life Scale (SWLS), and the Internally Displaced Persons Self-Esteem Questionnaire (ISEQ). All instruments were validated, and internal consistency was established using Cronbach’s Alpha, yielding coefficients of 0.73 for LNS, 0.88 for CTEI, 0.76 for SWLS, and 0.82 for ISEQ. The instruments were administered by the researcher in collaboration with trained research assistants. Data were analyzed using regression analysis. Findings: The results indicated that both psychological and educational adjustments significantly predicted the cognitive ability levels of internally displaced students in Physics. Furthermore, their combined predictive effect was also found to be statistically significant. Significance: Based on these findings, it was recommended that science educators tailor instructional content to align with the current cognitive and emotional needs of internally displaced learners, thereby facilitating improved psychological adjustment and academic performance.